Powierzchniowe Ogrzewanie Półprzestrzeni Warstwowej - Vodička, V. (Engineering Transactions, 1963)
The object of the paper is to determine the non-steady temperature field in the body x ≥ 0, - ∞ < y < ∞, - ∞ < z